Single suture craniosynostosis: Identification of rare variants in genes associated with syndromic forms. Issue 2 (23rd November 2017) - Clarke, Christine M.; Fok, Vincent T.; Gustafson, Jennifer A.; Smyth, Matthew D.; Timms, Andrew E.; Frazar, Chris D.; Smith, Joshua D.; Birgfeld, Craig B.; Lee, Amy; Ellenbogen, Richard G.; Gruss, Joseph S.; Hopper, Richard A.; et al.
Abstract : We report RNA‐Sequencing results on a cohort of patients with single suture craniosynostosis and demonstrate significant enrichment of heterozygous, rare, and damaging variants among key craniosynostosis‐related genes. Genetic burden analysis identified a significant increase in damaging variants in ATR, EFNA4, ERF, MEGF8, SCARF2, and TGFBR2 . Of 391 participants, 15% were found to have damaging and potentially causal variants in 29 genes. We observed transmission in 96% of the affected individuals, and thus penetrance, epigenetics, and oligogenic factors need to be considered when recommending genetic testing in patients with nonsyndromic craniosynostosis.